USAGE OF TRANSFORMATION AND COMBINATORY METHODS WHEN DEVELOPING NEW MODELS OF WOMAN’S EVENING GOWNS - Зубкова, Л. І.; Нестеренко , Л. Л.; Яценко, М. В. (Fashion Industry, 2025)
Purpose. Research the ways to use methods and elements of transformation and combinatory design approaches for developing new models. Methodology. Methods of project design for clothing collections (such as analysis, synthesis and graphic transformation), along with classification and systematization of information, were used in this work. Results. Techniques and elements of both transformation and combinatory methods have been used to expand the possibilities of designing modifiable items. As a result of systematization of various techniques, a collection of transformable evening gowns was created. This approach allows to not only save consumer money, but lower the utilization cost for used clothes. Scientific novelty. Systematization of transformation and combinatory techniques done in this work, based on design methods’ analysis, can be used in women’s clothes development with the purpose to extend the use to fit celebratory moments with better variety. Practical value. The use of transformation and combinatory methods has allowed me to design the collection of women’s evening gowns, where each item can be used in several variations.